Reliability Study of Fiber Coupling Efficiency of 980 nm Semiconductor Laser - Gang Liu; Shuhao Pang; Xin Zhang; Mingzhi Tang; Lei Liang; Rui Li; Rui Huang (Photonics)
In order to improve the stability of semiconductor laser fiber coupling efficiency, based on the coupling principle, the optimal parameters for semiconductor laser fiber coupling were simulated to be θ = 45°, r = 3.25 μm, and z = 5.65 μm. By optimizing the structure and position of the lens fiber, it has been experimentally proven that the maximum fiber coupling efficiency of the 980 nm semiconductor laser can reach 87.1%, and the average coupling efficiency can also reach 84%. After temperature cycling and aging experiments, the average coupling efficiency of the device was 81.7%, indicating a decrease in coupling efficiency. At the same time, the effect of fiber stress on the reliability of coupling efficiency was analyzed, and the stability and consistency of the device before and after temperature cycling were explored. In future work, it will be necessary to further optimize the thermal stress caused by UV glue curing and tail pipe soldering, find suitable process parameters, and obtain stable and reliable coupling modules.